Counselling skills in higher education: a case study of selected academic administrators - Hussien, Suhailah (Persatuan Kaunseling Malaysia, 2011)
The study examined the experiences of selected academic administrators of IIUM who were involved in student advising. The study involved an in depth qualitative approach,using individual interviews, focus group discussion and document analysis. The aims of the study were to identify the kinds of problems faced by the students, the nature of advice and assistance provided by the academic administrators to the students, and the knowledge and skills that the academic administrators needed in order to help the students. Data gathered were analysed using the thematic approach and guided by the objectives of the study. The findings of the study indicated that the students faced academic and discipline problems that were related to the students’ psychological, family, and relationship problems. The nature of advice and assistance that the academic administrators provided concerned academic and personal matters. It was found that the academic administrators lacked advising and helping skills. Thus, the study suggests that lecturers in higher education should be equipped with counselling skills and training should be provided as part of the academic staff professional development.